ANALYSIS OF THE LEAD (Pb) CONTENT IN SEDIMENT, SEA WATER AND BLOOD COCKLE Anadara granosa L. FROM THE COASTAL WATER OF MAKASSAR - Olivia Datu Parung; Magdalena Litaay; Eva Johannes (Marina Chimica Acta, 2015)
The research about analysis of the content of heavy metal lead (Pb) in sediment, sea waterand blood cockle Anadara granosa L. from the caostal water of Makassar has been done.This research was aimed to figure out the Pb content in the sediment, the sea water and theblood cockle A. granosa L. The sample was taken by using Purposive sampling method. Thesamples preparation used composite method and Pb level in samples was determined byAtomic Absorption Spectrofotometric (AAS). The result showed that at Tanjung Bunga, theaverage of Pb content in the: sea water 0,289 ppm, sediment 0,609 ppm and blood cockle A.granosa L. 0,704 ppm. In the Mangara Bombang, the average of Pb content in the sea water0,273 ppm but Pb level in the sediment and in the blood cockle A. granosa L. were notdetected.